COMPARATIVE STUDY OF RADIOLOGICAL AND FUNCTIONAL OUTCOME OF EXTRA ARTICULAR DISTALRADIUS FRACTURE TREATED CONSERVATIVELY WITH RESPECT TO ITS POSITION OF IMMOBILIZATION - Gnawali, Gopal Prasad (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Distal radius fracture is one of the common injury in orthopedic trauma. Traditionally,this fracture is being treated with closed reduction and immobilization in palmer flexion and ulnar deviation. This position of immobilization has been shown with poor functional result. So the aim of our study is to compare the radiological and functional outcome of distal radius fracture treated conservatively with respect to position of immobilization. MATERIAL AND METHODS: Hundred patients, all above 20 years of age with distal radius fracturewhere treated with closed reduction and below elbow cast application. Patients were randomly allocated to dorsal and palmer flexed plaster cast application, fifty in dorsiflexion group and fifty in palmer flexion group. All patients were followed up at 2nd week, 4th week, 6th week and 12th weeks. Radiological parameters measured in every follow-up and functional parameters measured after removal of cast in last two follow up. The results were scored and compared by Demerit Scoring System of Saito. For comparison, t test and Chi square test were used as necessary. RESULTS: All fractures united. All individual movements of wrist were significantly better in the dorsiflexed immobilized group as compared with the palmerflexed immobilized group. Radiological parameters were also markedly better in the dorsiflexed group. CONCLUSION: Both radiological and functional results of the extra articular distal radius fracture are better if the fracture immobilized in the dorsiflexed position after reduction rather than traditional palmer flexion position. Journal of Universal College of Medical Sciences Vol. 6, No. 1, 2018, page: 46-51